Example: 3 + 2 = 2 + 3 Let, LHS, 3 + 2 = 5 RHS, 2 + 3 = 5 Therefore, LHS = RHS. |

Example: 2 x 3 = 3 x 2 Let, LHS, 3 x 2 = 6 RHS, 2 x 3 = 6 Therefore, LHS = RHS. |

Example: 2 + (3 + 4) = (2 + 3) + 4 Let, LHS, 2 + (3 + 4) = 2 + (7) = 9 RHS, (2 + 3) + 4 = 5 + 4 = 9 Therefore, LHS = RHS. |

Example: 2 x (3 x 4) = (2 x 3) x 4 Let, LHS, 2 x (3 x 4) = 2 x (12) = 24 RHS, (2 x 3) x 4 = 6 x 4 = 24 Therefore, LHS = RHS. |

Example: 2 x (3 + 4) = (2 x 3) + (2 x 4) LHS, 2 x (3 + 4) = 2 x (7) = 14 RHS, (2 x 3) + (2 x 4) = 6 + 8 = 14 Therefore, LHS = RHS. |

Example: 2 + 0 = 2 LHS = 2 + 0 = 2 = RHS |

Example: 2 x 1 = 2 LHS = 2 x 1 = 2 = RHS |

Example: 2 + (-2) = 0 LHS = 2 + (-2) = 2 – 2 = 0 = RHS |

Example: 2 x 2 LHS = 2 x 1/2 = 1 = RHS |

Example: 2 x 0 = 0 LHS = 2 x 0 = 0 = RHS |

# Number Properties

Advertisements

Pingback: Tips & Tricks – Breath Math